Neoliberalizm i desekularyzacja jako dwa wymiary reform edukacji we współczesnej Turcji - Hildebrandt-Wypych, Dobrochna (Wydawnictwo Naukowe UAM, 2017)
The text focuses on neoliberalism and desecularisation as two major dimensions of social and educational change in contemporary Turkey. Key educational reforms of recent years are discussed from the perspective of the conservative-religious turn in Turkish society and politics, particularly noticeable from 2002, i.e. the first AKP electoral success. However, the origins of the Oriental-Western duality of identity, as well as the “use” of Islam for strengthening the new Turkish national identity, can be traced back to Kemalist policy of secularisation and modernization of Turkish society. This peculiar merge of neoliberal and religious symbols is also visible in education, where selforientalizing, nationalizing and secularizing discourses mix with the pressure on selection, effectiveness and competition in the “western” style. Therefore, the rising importance of faith schools in present day Turkey has also been discussed in the light of the historical Kemalist concept of transformation of Islam and the creation of national, state-controlled “civic religion”.
Neoliberalism and Desecularisation as Two Dimensions of Educational Reforms in Contemporary Turkey
Keywords: Turkey; educational reforms; faith schools; Imam Hatip; neolibaralism; secularisation; desecularisation; educational policy